2017
DOI: 10.1136/emermed-2016-206199
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of youth agreeing to electronic sexually transmitted infection risk assessment in the emergency department

Abstract: Objectives Adolescents and young adults are at high risk for sexually transmitted infections (STIs). We previously reported an increase in STI testing of adolescents in our ED by obtaining a sexual history using an Audio-enhanced Computer-Assisted Self-Interview (ACASI). We now examine associations among demographics, sexual behaviour, chief complaint and willingness to be tested. Methods This was a prospective study conducted in a paediatric ED between April and December 2011. After triage, eligible patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, the literature supports that adolescents are open to risk-behavior screening in the ED regardless of their chief complaint. Studies have found acceptability for both specific risk behaviors such as substance abuse; 15 pregnancy prevention; 33 sexually transmitted infection risk; [34][35][36] depression; 37 suicidality; 38 and for comprehensive screening across a battery of five risk behaviors (substance use, violence, depression, human trafficking, and access to firearms). 39 Risk behavior screening in the ED is an important tool for adolescent health as it can reach a population that does not frequently access preventive healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature supports that adolescents are open to risk-behavior screening in the ED regardless of their chief complaint. Studies have found acceptability for both specific risk behaviors such as substance abuse; 15 pregnancy prevention; 33 sexually transmitted infection risk; [34][35][36] depression; 37 suicidality; 38 and for comprehensive screening across a battery of five risk behaviors (substance use, violence, depression, human trafficking, and access to firearms). 39 Risk behavior screening in the ED is an important tool for adolescent health as it can reach a population that does not frequently access preventive healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…This is a relevant issue, as adolescents and adults in both the pediatric ED and other settings have indicated they prefer answering questions regarding their sexual history via electronic questionnaire, and in some instances, they provide more comprehensive and accurate information using electronic questionnaires. 13,[30][31][32][33][34][35][36][37] Thus, the preference expressed by most ED directors we surveyed to gather this kind of sensitive information during faceto-face interviews seems questionable. Based on these findings, ED physicians likely will need to adjust both their individual practice and ED workflows to accommodate expanded reproductive healthcare interventions in the pediatric ED.…”
Section: Discussionmentioning
confidence: 99%
“…This could include the use of varying approaches to screening and HIVST delivery either through digital interfaces as has been used in other sexually transmitted infection research, 55 or via more traditional patient-provider interactions. As well, the consideration of how ED-based HIVST programs best incorporate into the HIVspecific, and broader public health agendas from clinical applications and cost valuation perspectives in a given setting are key, as has been highlight by prior emergency care consensus recommendations.…”
Section: Limitationsmentioning
confidence: 99%